FORMATION OF PROFESSIONAL-MODERN COMPETENCIES OF PRIMARY SCHOOL TEACHERS (Web of Teachers: Inderscience Research, 2025)
This article focuses on the theoretical and practical aspects of forming professional-modern competencies of primary school teachers. The concept of competency, its role in the personal and professional growth of teachers, and issues of improving education quality through innovative technologies and modern approaches are analyzed.